2008
DOI: 10.1001/archpedi.162.10.916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prior Stimulant Treatment for Attention-Deficit/Hyperactivity Disorder on Subsequent Risk for Cigarette Smoking and Alcohol and Drug Use Disorders in Adolescents

Abstract: Objective Controversy remains over the effect of stimulant treatment on later substance use disorders (SUD). To this end, we examined the risk imparted by stimulant treatment for attention-deficit/hyperactivity disorder (ADHD) on SUD and nicotine dependence in a study of girls with ADHD. Design case-controlled, prospective, five-year follow up study. Participants adolescent girls with and without ADHD from psychiatric and pediatric sources. Setting Massachusetts General Hospital. Blinded interviewers det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 38 publications
4
85
0
3
Order By: Relevance
“…Son de interés para los clínicos los estudios los que describen que el tratamiento del TDAH con fármacos estimulantes previene el riesgo de desarrollar TUS, en hasta un 50% (Katusic et al, 2005;Wilens, Faraone, Biederman y Gunawardene, 2003;Wilens et al, 2008).…”
Section: Drug Treatmentunclassified
See 3 more Smart Citations
“…Son de interés para los clínicos los estudios los que describen que el tratamiento del TDAH con fármacos estimulantes previene el riesgo de desarrollar TUS, en hasta un 50% (Katusic et al, 2005;Wilens, Faraone, Biederman y Gunawardene, 2003;Wilens et al, 2008).…”
Section: Drug Treatmentunclassified
“…En un estudio controlado con placebo sobre los efectos de la atomoxetina en adultos con TDAH dependientes de alcohol, se ha demostrado que este fármaco se asocia a una mejoría de los síntomas del TDAH, sin embargo, los datos sobre los efectos en el consumo de alcohol fueron inconsistentes (Wilens et al, 2008). Al analizar la seguridad del fármaco, se observó que los pacientes alcohólicos con TDAH no difieren en la adherencia al tratamiento de los pacientes alcohólicos sin TDAH.…”
Section: Drug Treatmentunclassified
See 2 more Smart Citations
“…Attention-enhancing drugs such as methylphenidate and atomoxetine boost the activity of key receptor systems in the prefrontal cortex, in particular those for noradrenaline and dopamine. Some evidence already suggests that patients with ADHD are less likely to go on to abuse drugs if they are receiving medication for their condition 7 . And earlier this year, a team led by Daina Economidou at the University of Cambridge, UK, reported that atomoxetine helped rats with an ADHD-like impulsivity to resist a relapse to cocaine-seeking 8 .…”
Section: Quenching the Flamementioning
confidence: 99%